Youtube Independent Music Video Artist: Learning, Production and Exhibition in Digital Space - Romdhi Fatkhur Rozi; Rachmah Ida; Budi Irawanto (Seni Media Rekam ISI Surakarta, 2023)
Music videos by independent musicians represent a new portrait of the music industry in the digital era. This article tries to look at how YouTube has influenced the learning patterns, production patterns, and performance patterns of music content creators in the digital space. A review of the literature in this study connects art, technology, and the media. The research method used is a case study with the object of two independent music channels, Jember on YouTube. The data was obtained through creator interviews and observations of independent music channels, as well as library studies, which were then tested for validity by triangulation of sources. Qualitative data analysis is done descriptively. The findings reveal how content creators start their channels, gain popularity, interact with subscribers, and promote their music careers through YouTube. There was a rather fundamental paradigm shift in the concept of amateur musicians and professional musicians as YouTube became a digital space to be counted on for sharing artwork. Advanced research is recommended to focus on the influence of the YouTube platform on culture, capital economic issues, economy sharing, its exposure to the audience, and its function as a source of learning. Keywords: YouTube; digital learning; production; exhibition; space